Analysis of redundancy protocol stack TCP / IP - Дрововозов, В. І.; Хемраев, А. К. (Problems of Informatization and Control, 2013)
Analysis of share performance information in a network packet that passes through the protocol stack TCP / IP, and the estimation of the impact and value pack size overhead and payload performance of computer networks. The possible ways to improve the performance of computer networks and their application problems using wireless networking